1995
DOI: 10.1128/jvi.69.11.6652-6657.1995
|View full text |Cite
|
Sign up to set email alerts
|

Functions of the internal pre-S domain of the large surface protein in hepatitis B virus particle morphogenesis

Abstract: The large hepatitis B virus (HBV) surface protein (L) forms two isomers which display their N-terminal pre-S domain at the internal and external side of the viral envelope, respectively. The external pre-S domain has been implicated in binding to a virus receptor. To investigate functions of the internal pre-S domain, a secretion signal sequence was fused to the N terminus of L (sigL), causing exclusive expression of external pre-S domains. A fusion construct with a nonfunctional signal (s25L), which correspon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(44 citation statements)
references
References 33 publications
2
42
0
Order By: Relevance
“…Previous studies based on cell transfection with HBV mutants for the L protein suggested that it is retained in the ER as a transmembrane protein because of binding to a cytosolic factor. 16 In a recent study, the L protein alone was found to form intravesicular 20-nm spherical particles identical to the S and M protein particles but retained in intracellular compartments by calnexin. 17 Nevertheless, the so-called ground-glass appearance of the hepatocytes in chronic HBV infection seems to be caused by the intracellular accumulation of L-protein-rich filaments.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies based on cell transfection with HBV mutants for the L protein suggested that it is retained in the ER as a transmembrane protein because of binding to a cytosolic factor. 16 In a recent study, the L protein alone was found to form intravesicular 20-nm spherical particles identical to the S and M protein particles but retained in intracellular compartments by calnexin. 17 Nevertheless, the so-called ground-glass appearance of the hepatocytes in chronic HBV infection seems to be caused by the intracellular accumulation of L-protein-rich filaments.…”
Section: Discussionmentioning
confidence: 95%
“…The pre-S domain has been shown to be necessary for viral budding at the ER. 16 Despite this complex configuration of the pre-S region, mutations including deletion and insertion are found frequently in chronic HBV carriers. 18,[27][28][29] The selection pressure resulting in pre-S mutations is not as obvious for mutations found in the ''a'' determinant of the S-gene.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it is necessary that the pre-S domain passes through the membrane, and in the mature virion, half of the pre-S domains are located either inside or outside of the viral envelope. 16,17 The complex function of the pre-S domain and the different levels of regulation indicate that the virus uses this small region very efficiently. However, naturally occurring mutants in the pre-S region are found frequently, and they seem to correlate with a more progressive form of liver disease (Locarnini S, McMillan J, personal communication, November, 1998).…”
mentioning
confidence: 99%
“…Unlike some Lentivirinae able to bud through a lipid bilayer without any envelope protein (Hourioux et al, 2000), the HBV nucleocapsid budding is strictly dependent on the large L protein. The absence of L or its in vitro production under an exclusive 'e-preS' topology completely abolish the generation of new virions (Bruss and Vieluf, 1995). Indeed, the 'i-preS' topology of L is obligatory for mature HBV nucleocapsid recruitment.…”
Section: Hbv Morphogenesismentioning
confidence: 99%